SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN BEDAK WAJAH DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Haryo Kusumo; sindu rakasiwi (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2020)
Abstract The development of the cosmetics industry continues to increase causing a variety of cosmetic products issued in the market, both in terms of brands, facilities, types, and other variations contained in these products. Facial skin is the most important part of a woman's appearance to ensure that the skin always looks smooth and healthy. By adding face powder brands offered to consumers, they are increasingly confused in choosing the right face powder. The development of information technology that forms a support system can help consumers determine the right face powder. The method used is SAW (Simple Additive Weighting). The basic concept of the SAW method is to find a weighted sum of performance evaluations for each alternative on all attributes. The criteria used are age, skin type, brand, price, composition, aroma, size, color and shape of the packaging. From the results of the validation test conducted by the system expert shows the final value of the calculation is 3.0, the system is declared valid. While from the validation test results, the expert gets the final calculation material is 3.5 and the material expert approves the appropriate system because the system can provide appropriate recommendations for new consumers. From the validity and reliability test results obtained from 10 assessment indicator items, there are 8 question items that are considered valid and 8 items assessment indicators can be trusted.